Light yield non-proportionality of inorganic crystals and its effect on cosmic-ray measurements. (1st August 2022) - Adriani, O.; Berti, E.; Betti, P.; Bigongiari, G.; Bonechi, L.; Bongi, M.; Bottai, S.; Brogi, P.; Castellini, G.; Checchia, C.; D'Alessandro, R.; Detti, S.; et al.
Abstract: The multi-TeV energy region of the cosmic-ray spectra has been recently explored by direct detection experiments that used calorimetric techniques to measure the energy of the cosmic particles. Interesting spectral features have been observed in both all-electron and nuclei spectra. However, the interpretation of the results is compromised by the disagreements between the data obtained from the various experiments, that are not reconcilable with the quoted experimental uncertainties. Understanding the reason for the discrepancy among the measurements is of fundamental importance in view of the forthcoming high-energy cosmic-ray experiments planned for space, as well as for the correct interpretation of the available results. The purpose of this work is to investigate the possibility that a systematic effect may derive from the non-proportionality of the light response of inorganic crystals, typically used in high-energy calorimetry due to their excellent energy-resolution performance. The main reason for the non-proportionality of the crystals is that scintillation light yield depends on ionisation density. Experimental data obtained with ion beams were used to characterize the light response of various scintillator materials. The obtained luminous efficiencies were used as input of a Monte Carlo simulation to perform a comparative study of the effect of the light-yield non-proportionality on the detection of high-energy electromagnetic and hadronic showers. The result of this study indicates that, if the calorimeter response is calibrated by using the energy deposit of minimum ionizing particles, the measured shower energy might be affected by a significant systematic shift, at the level of few percent, whose sign and magnitude depend specifically on the type of scintillator material used.